Comparative characteristics of the content of music education of standard curricula for primary schools in Kazakhstan, the UK and Singapore - Кульманова, Шолпан; Құлманова, Шолпан (Pedagogy and Psychology, 2022)
Abstract The processes of change in the field of education in our country are becoming universal, which increases the relevance of conducting a comparative analysis of world experience in the development of education. This article discusses in detail the content of the current standard curriculum for the subject «Music» for grades 1-4 level of primary education in Kazakhstan from 2018. The authors presented the most priority educational positions aimed at fostering Kazakhstani patriotism, moral and aesthetic attitude to national and universal values, and the development of musical and creative abilities. In the same way, a detailed analysis of the music education of primary schools,recognized throughout the world in such countrie as the United Kingdom and Singapore, is presented. The study of the content of standard music curricula for primary classes in these countries enabled the authors to identify the most valuable ideas of foreign musical and pedagogical experience. The article presents a set of means, methods and techniques of comparative pedagogy, which allowed the authors to conduct research in accordance with the stated goal. On the basis of the theoretical studies were identified peculiarities of the development of music programs for primary school of the above countries. The authors point to certain differences in the structure of programs, in the presentation of educational musical material, which are associated with the national characteristics and culture of each country. At the same time, they focus on the fact that in the updated content of the current model curriculum for music of our country, from 2018, there is a certain similarity with foreign programs, based on a comparative analysis. This similarity is manifested in common approaches to the selection of the content of musical knowledge, which are carried out in conjunction with the new generation of educational and computer technology, as well as in the education of children through music love and respect for the culture of their people and the culture of other peoples. Keywords: music, education, curriculum, Kazakhstan, United Kingdom, Singapore, subject of music, class, training, purpose, tasks, method of comparison